Przekłady literatury macedońskiej w Polsce i polskiej w Macedonii w latach 2007—2013 - Błaszak, Magdalena (Przekłady Literatur Słowiańskich, 2014)
Translations of Macedonian literature in Poland and Polish one in Macedonia in 2007—2013 This article presents an analysis of translations of Polish literature in Macedonia and the Macedonian one published in Poland in 2007—2013. It contains book editions as well as translations published in magazines. The author tries to answer the question why do the translators choose for translation the books of certain writers. The conclusion is that the most common selection criterion is honoring the publication of a literary award. After analyzing the author notes that over the years the number of translations of Polish literature in Macedonia and Macedonian one in Poland increases. Key words: Translation, literary prize, Polish literature, Macedonian literature.